2021
DOI: 10.1111/ced.14658
|View full text |Cite
|
Sign up to set email alerts
|

Establishing the efficacy and safety of the novel use of common salt for the treatment of pyogenic granuloma

Abstract: Summary Background Recurrent bleeding episodes are often a cause of significant anxiety in patients with pyogenic granuloma (PG). The idea of using common salt for the treatment of PG arose from the need for a relatively safe and effective treatment because of the recurrent nature of the lesion. Methods A prospective open‐label uncontrolled study of 50 patients was conducted. All cases were treated with ordinary table salt from a commercially available package. White soft paraffin was first applied over the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Among the non-surgical treatment options, liquid nitrogen is used most often and has the lowest overall recurrence rate, followed by carbon dioxide laser ablation and flashlamp pulsed dye laser therapy. 4,5 Salt has been recently described as a treatment for PG. Daruwalla et al reported a case in which a pinch of salt was applied to a lesion, soft white paraffin was applied at the lesion margins to prevent perilesional skin irritation, and the lesion was covered with a surgical adhesive tape.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Among the non-surgical treatment options, liquid nitrogen is used most often and has the lowest overall recurrence rate, followed by carbon dioxide laser ablation and flashlamp pulsed dye laser therapy. 4,5 Salt has been recently described as a treatment for PG. Daruwalla et al reported a case in which a pinch of salt was applied to a lesion, soft white paraffin was applied at the lesion margins to prevent perilesional skin irritation, and the lesion was covered with a surgical adhesive tape.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 95% of the patients stated that they would repeat salt therapy for any recurrences of PG, and the remaining 5% of patients stated that they would prefer a treatment that provided faster results. 4 Salt application to PG creates a hyperosmolar tissue environment that leads to lesion shrinkage due to a desiccant effect. 2,3 Salt has also been used to treat umbilical granulomas with an efficacy comparable to that achieved with silver nitrate, copper sulfate, and surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4] It affects all ages but is more often in children and young people. 4,5 Although its nature is benign, it is characterized by fast growth and recurrent bleeding periods. 5 Most of the time, it appears as a unique pediculated lesion but multiples tumors also are detected.…”
mentioning
confidence: 99%